Question
upstudy study bank question image url

Solve using elimination, \[ \begin{array}{l}-8 x-6 y=12 \\ -6 x-6 y=18\end{array} \]

Ask by Chandler Donnelly. in the United States
Feb 19,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution is \( x=3 \) and \( y=-6 \).

Solution

Solve the system of equations \( -8x-6y=12;-6x-6y=18 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}-8x-6y=12\\-6x-6y=18\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-\frac{6+3y}{4}\\-6x-6y=18\end{array}\right.\) - step2: Substitute the value of \(x:\) \(-6\left(-\frac{6+3y}{4}\right)-6y=18\) - step3: Multiply the terms: \(\frac{3\left(6+3y\right)}{2}-6y=18\) - step4: Multiply both sides of the equation by LCD: \(\left(\frac{3\left(6+3y\right)}{2}-6y\right)\times 2=18\times 2\) - step5: Simplify the equation: \(18-3y=36\) - step6: Move the constant to the right side: \(-3y=36-18\) - step7: Subtract the numbers: \(-3y=18\) - step8: Change the signs: \(3y=-18\) - step9: Divide both sides: \(\frac{3y}{3}=\frac{-18}{3}\) - step10: Divide the numbers: \(y=-6\) - step11: Substitute the value of \(y:\) \(x=-\frac{6+3\left(-6\right)}{4}\) - step12: Substitute back: \(x=\frac{-6+3\times 6}{4}\) - step13: Calculate: \(x=3\) - step14: Calculate: \(\left\{ \begin{array}{l}x=3\\y=-6\end{array}\right.\) - step15: Check the solution: \(\left\{ \begin{array}{l}x=3\\y=-6\end{array}\right.\) - step16: Rewrite: \(\left(x,y\right) = \left(3,-6\right)\) The solution to the system of equations using elimination is \( (x,y) = (3,-6) \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the system of equations using elimination, we start with the two equations: 1) \(-8x - 6y = 12\) 2) \(-6x - 6y = 18\) We can eliminate \(y\) by subtracting the second equation from the first. First, let's multiply the second equation by 1 (to keep it the same) and align the terms: \[ \begin{array}{rcl} -8x - 6y & = & 12 \\ -6x - 6y & = & 18 \end{array} \] Subtract the second equation from the first: \[ (-8x - 6y) - (-6x - 6y) = 12 - 18 \] This simplifies to: \[ -8x + 6x - 6y + 6y = -6 \] which can be simplified further to: \[ -2x = -6 \] Dividing both sides by -2 gives: \[ x = 3 \] Now that we have the value for \(x\), we can substitute \(x = 3\) back into one of the original equations to find \(y\). Let’s use the second equation: \[ -6(3) - 6y = 18 \] This simplifies to: \[ -18 - 6y = 18 \] Add 18 to both sides: \[ -6y = 36 \] Dividing both sides by -6 gives: \[ y = -6 \] The solution to the system of equations is \(x = 3\) and \(y = -6\). Final answer: \( \boxed{(3, -6)} \)

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy